Phenolic compounds level in leaves of chestnut horse in different periods of environmental stress development - Свідзінська, Н. Б.; Попова, Е. М.; Вініченко, О. В. (Problems of Environmental Biotechnology, 2015)
The changes accumulation of phenolic compounds in the leaves of horse chestnut Aesculus hippocastanum L. in different periods of environmental stress on Victory Avenue near the city. Kyiv.